2009 IEEE 9th International Conference on the Properties and Applications of Dielectric Materials 2009
DOI: 10.1109/icpadm.2009.5252245
|View full text |Cite
|
Sign up to set email alerts
|

Space charge characteristics of multi-layer oil-paper insulation under different DC voltages

Abstract: Abstract:In this paper, space charge in oil-paper insulation system has been investigated using the pulsed electroacoustic (PEA) technique. A series of measurements were carried out when the insulation system was subjected to different applied voltages. Charge dynamics in the insulation system during the volts-on, volts-off and decay have been analyzed. It has been found that homocharge injection occurred both at the anode and the cathode. Positive charges are observed to accumulate in the layers, which indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Considerable research works [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been done on the mechanism of dielectric degradation and space charge characteristics of transformer insulation paper especially in cellulose paper and oil-immersed Nomex insulation paper. Liuet al [18] measured the space charge distribution of oil-impregnated synthetic fibreboard with different moisture contents at room temperature and indicated that the space charge characteristics of insulation paper would change within the difference of moisture contents.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research works [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been done on the mechanism of dielectric degradation and space charge characteristics of transformer insulation paper especially in cellulose paper and oil-immersed Nomex insulation paper. Liuet al [18] measured the space charge distribution of oil-impregnated synthetic fibreboard with different moisture contents at room temperature and indicated that the space charge characteristics of insulation paper would change within the difference of moisture contents.…”
Section: Introductionmentioning
confidence: 99%